Physiotherapy in family health strategy: perception of users - Rocha Júnior, Paulo Roberto; Moreira, Luciane Marquesini (Journal of Health Care, 2016)
Introduction and objective: This study aimed to examine the perceptions of users about the action of physiotherapy in the Family Health Strategy (FHS). Materials and methods: Participated in the research eight (n=8) individuals that have been assisted by an internship in preventive physiotherapy in FHS. For data collection we used semi-directive interviews, in which the following categories of analysis emerged and were thus divided: "validating the physiotherapist in the FHS" and "considerations of the role of the physiotherapist in the FHS: with the word, the users". Results and conclusion: Users interviewed are unanimous about the importance of the physical therapist in composing ESF teams, and, in doing so, contribute with their knowledge to the quality of care.